Negative film plot and tourists' image and intentions: the case of City of God - Loureiro, S. M. C.; de Araújo, A. F. B. (Journal of Travel and Tourism Marketing, 2015)
This study aims to contribute to the understanding of the effects of films with a negative plot on tourists’ cognitive and affective image about Brazil and behavioral intentions of visiting the country. The film selected is City of God, one of the most internationally acclaimed motion pictures produced in Brazil. The results suggest that films with a negative plot tend to negatively reinforce the viewers’ evaluations of the image attributes, although the influence on the general image tends to be subtle. Moreover, it was concluded that in the case of films with a negative plot, the imagery of landscapes is the element that is most likely to increase visiting intention.